KEEFEKTIFAN PEMBELAJARAN MISSOURI MATHEMATICS PROJECT DENGAN PENDEKATAN PROBLEM SOLVING TERHADAP KEMANDIRIAN BELAJAR DAN KEMAMPUAN KOMUNIKASI MATEMATIS - Baharuddin; Khadijah (LPPM Universitas Muhammadiyah Muara Bungo, 2024)
The aim of this study is to describe (1) the effectiveness of Missouri Mathematics Project learning with problem solving approach on independent learning and mathematical communication skills of students, (2) the effectiveness of Missouri Mathematics Project learning on independent learning and mathematical communication skills of students, and (3) the differences of effectiveness of MMP-PS learning with MMP on independent learning and mathematical communication skills of students. This research approach is quantitative with a quasi-experimental type of research. The effectiveness of MMP-PS and MMP learning on independent learning and mathematical communication skills used one sample t test. The differences of effectiveness of MMP-PS learning with MMP on independent learning and mathematical communication skills of students were analyzed using MANOVA. The results of the study indicate that MMP-PS learning is effective in independent learning and mathematical communication skills of students. MMP learning is ineffective on independent learning, but it is effective for mathematical communication skills. In addition, there are differences of effectiveness between MMP-PS and MMP learning on independent learning and students' mathematical communication skills. The results of further tests indicate that Missouri Mathematics Project learning with a problem solving approach is more effective than Missouri Mathematics Project learning on independent learning and mathematical communication skills of students.